2018
DOI: 10.1063/1.5050166
|View full text |Cite
|
Sign up to set email alerts
|

Histologic observation, identification, and secondary metabolites analysis of endophytic fungi isolated from a medicinal plant, hedychium acuminatum Roscoe

Abstract: Abstract. Some endophytic fungi live in medicinal plant tissue and could produce some secondary metabolites. This research was done to 1) determine the endophytic fungi position in the Hedychium acuminatum Roscoe. plant tissue by histological observation, 2) identify the endophytic fungi species isolated from the rhizome, leaf sheath, and the leaf of H. acuminatum, and 3) analyze the contents of some secondary metabolites that be produced by the endophytic fungi species isolated from H. acuminatum. The determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…Some endophytic fungi species isolated from P. angulata plant could be found in another plant. Colletotrichum alienum also found as one of the endophytic fungi species isolated from Hedycium acuminatum (Hastuti et al 2018), from Cananga odorata (Hastuti et al 2019a). Another species of Colletotrichum have been isolated from Piper nigrum, i.e: Colletotrichum gloeosporoides (Chitra et al 2014), in tomato fruit, i.e: Colletotrichum acutatum (Zivkovic et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some endophytic fungi species isolated from P. angulata plant could be found in another plant. Colletotrichum alienum also found as one of the endophytic fungi species isolated from Hedycium acuminatum (Hastuti et al 2018), from Cananga odorata (Hastuti et al 2019a). Another species of Colletotrichum have been isolated from Piper nigrum, i.e: Colletotrichum gloeosporoides (Chitra et al 2014), in tomato fruit, i.e: Colletotrichum acutatum (Zivkovic et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In the previous research it was found an endophytic fungi: Penicillium sp, isolated from Curcuma longa produced an antimicrobial compound (Singh et al 2014). Another research proved that some endophytic fungi, i.e: Fusarium oxysporum, Rhizoctonia sp., Fusarium solani, Colletotrichum alienum, Colletotrichum ti, Colletotrichum aotearoa, Aspergillus parasiticus, Hansfordia biophila, Fusarium semitectum, Colletotrichum coccodes, and Colletotrichum gloeosporoides isolated from Hedychium acuminatum could produced antibacterial compounds: alkaloid, flavonoid, terpenoid, and tannin in the secondary metabolites (Hastuti et al 2018). It is also proved that the secondary metabolites produced by those endophytic fungi species isolated from H. acuminantum have antimicrobial activity towards Staphylococcus aureus, and Bacillus subtilis (Hastuti et al 2019b).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…It assumed that endophytes colonizing plant tissue play an important role in synthesizing of biologically active compounds and protecting plants from soil-borne disease ( Cho et al., 2015 ). The diversity of endophytic microbes associated with medicinal plant species such as Aloe vera, Mentha arvensis, Dracaena cochinchinensis, Hedycium acuminatum, Armoracia rusticana, Hypericum perforatum and others, and their biological activity were reported ( Salam et al., 2017 ; Hastuti et al., 2002 ; Egamberdieva et al., 2017 , 2020a ; Shurigin et al. 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…Endophytes use several mechanisms to support plant health, including the production of phytohormones [25] [27] , 1-aminocyclopropane-1-carboxylate (ACC) deaminase [28] , hydrogen cyanide [29] , [30] and induced systemic resistance [31] [33] . The diversity of endophytic microbes associated with medicinal plant species such as Aloe vera , Mentha arvensis , Dracaena cochinchinensis , Hedycium acuminatum, Armoracia rusticana , and others, were reported [34] [36] . Although several studies reported on the phytochemical constituents and biological activity of marigold ( C. officinalis L.), to date, there have been no reports of endophytes associated with marigold and their biological properties.…”
Section: Introductionmentioning
confidence: 99%